BEBERAPA FAKTOR YANG MEMPENGARUHI PRAKTIK IBU DALAM PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PEGANDAN KOTA SEMARANG - Rylas Chintya Aksamala; Bagoes Widjanarko; Anung Sugihantono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The number of EBF percentage in Pegandan Health Center on the last 3 years were still low and below the target. The number of EBF percentage on 2017 was 40,96% with EBF achievements (E6) reaching 15.13%. This study aims to analyze factors affecting the practice of exclusive breastfeeding.This research is a quantitative research with cross sectional approach. The sample was chosen using total sampling that is equal to 61 moms that have children aged 7-12 months. The data were collected through interviews using questionnaires. Data analysis was done univariate, bivariate, and multivariate.Most of the respondents were not practicing EBF (62,3%). The majority of respondents aged 20-35 (85,2%), had a problems on lactation process (67,3%), and have bad knowledge of EBF (54,1%). The result of bivariate analysis shows that there is a significant correlation between knowledge (p=0,000), attitude (p=0,001), family support (p=0,004), and cadres support (p=0,032).